La méthode d’Approfondissement et d’Apaisement Émotionnel (AAE) : une perspective pour comprendre, expliciter et réguler l’émotion - Sophie Thibauville (Perspectives Interdisciplinaires sur le Travail et la Santé)
While emotional labor is often presented as a commercial activity in professional circles, in this article it is considered to be a reflective and regulatory endeavour that takes place during the sharing and accompaniment of emotions. At the crossroads of work psychology and health, this article presents a methodological device for the explanation and regulation of emotions, namely the deep emotional understanding and relief method (DER). It was initially developed during research into emotions arising during periods of professional and/or life transition. In line with ethical and epistemological concerns, the method was longitudinally deployed in two major study phases between 2015 and 2022. The analyses highlighted the "awareness-raising" and "empowering" qualities of emotional work which contribute to the development of resources which in turn foster psychological well-being, particularly with regard to change.